Business Design And Business Implementation In Mo.Dessert Businesses - Wiranda Nur Aisyah; Anas Hidayat (Citakonsultindo, 2024)
The aim of writing this final assignment is to test the implementation of a business design for dessert box desserts with a focus on marketing through the Word of Mouth approach and marketing via social media. The aim of writing this final assignment is to develop an effective approach to increase brand awareness, consumer engagement and sales by maximizing effective production and marketing processes, as well as providing added value to products. The research results show that integrating Word of Mouth strategies, such as customer testimonials and personal recommendations, with social media marketing, such as creative campaigns and content sharing, can increase brand visibility and appeal. In addition, marketing strategies with loyalty card programs can stimulate repeat purchases, extend customer lifetime value, and strengthen the relationship between customers and brands.